Tree Based Protocol for Key Management in Wireless Sensor Networks - Aliouat M; Seba H; Messai M-L (EURASIP Journal on Wireless Communications and Networking, 2010)
Securing a wireless communication has generally a vital importance, particularly when this communication is in a hostile environment like in wireless sensor networks (WSNs). The problem is how to create cryptographic keys between sensor nodes to ensure secure communications. Limited resources of sensor nodes make a public key cryptosystem such as RSA not feasible. So, most solutions rely on a symmetric cryptosystem. In this paper, we propose a new key management scheme based on symmetric cryptography which is well adapted to the specific properties of WSNs. The evaluation of our solution shows that it minimizes memory occupation, ensures scalability, and resists against the hardest attack: compromised nodes.